A novel interlayer cleaning methods for improving internal quality in wire-arc directed energy deposition: processing, characterisation and performance demonstration - Hao Liu; Fan Jiang; Cheng Li; Ruican Zhu; Wei Liu; Di Yang; Zhihe Xu; Cheng Zhang; Shujun Chen; Bing Bai (Virtual and Physical Prototyping, 2025)
To address the surface oxidation and porosity defects in the wire-arc directed energy deposition of aluminum alloys, a laser-arc composite cleaning method is proposed for the irregular surface morphology of the deposited layer during the deposition process. The study analyzed the microscopic morphology of the surfaces after various cleaning methods and the changes in surface oxygen content, exploring the complementary rules and enhancement mechanisms of laser and electric arc cleaning in combined cleaning, as well as the optimal process parameter matching strategy. The effectiveness of the cleaning methods was evaluated by testing the porosity of the secondary deposited specimens after cleaning. The uncleaned specimens exhibited a porosity of 2.81%. Laser cleaning reduced this to 2.11%, while arc cleaning achieved 0.13%. The most significant reduction came from composite cleaning, with a minimum porosity of 0.05%. This indicates that composite cleaning can effectively reduce the porosity defects in additive manufacturing.